COMPARATIVE ANALYSIS OF CONTEMPORARY AND CLASSICAL TAFSIR QURAN - Siti Muhibah; Juhrah M. Arib; Siti Rohmah (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Classical Quranic interpretation is a way of interpreting the holy book of Islam that comes from the research of previous scholars, based on traditional principles including the scope of the Arabic language, the historical context of the revelation of verses, and the hadith of the Prophet Muhammad, among other sources that are considered authentic and authoritative. While modern tafsir is a contemporary approach to understanding the Quran that applies hermeneutics, social analysis, and cutting-edge scientific perspectives to answer new issues and the dynamics of today's life, while still adhering to the basic principles of Islam and often trying to connect classical texts with modern realities. The research method used in this study is the literature study method. The results show that despite the differences between classical and modern tafsir, they have great potential to complement each other. Classical tafsir, with its rich historical roots and methodology, provides the basis for a deep and authentic understanding of the teachings of the Quran. On the other hand, modern tafsir, through a more flexible and responsive approach to the times, offers insights that are adaptive and relevant to the current social, political and scientific context. The combination of these two approaches not only enriches the understanding of Islam, but also facilitates the application of Quranic teachings in the context of contemporary life.